Avaliação genotóxica e mutagênica do óleo essencial de Schinus terebinthifolius e estudo de sua ação antifúngica contra Colletotrichum gloeosporioides in vitro e in vivo - Grippa, Gabriela de Almeida (2009)
Schinus terebinthifolius is a plant popularly known as Brazilian peppertree and occurs in the vegetation of restinga. It is used in the popular medicine and the national and international cookery.In this work have been analyzed the genotoxic and mutagenic potential of the essential oil extracted from the fruit by means of the chromosomic aberration test in Allium cepa and the micronucleus test in Chinese hamster ovary cells (CHO-K1). The results had shown that the different tested concentrations of the oil did not have significant differences from the negative control, which demonstrates a genotoxic and mutagenic effect absence in both test systems. Therefore, the use of this oil is secure, with regard to the genotoxicity, in the studied concentrations (0.05, 0.10, 0.50, 1.00 and 2.39%). The genotoxic potential of the surfactant Tween 80, used to dilute the essential oil, was also investigated by chromosomic aberration test in A. cepa. The concentrations 1, 2, 3, 4, 5, 6, 7 and 8% have been evaluated and there was no significant differences between these and the negative control, which demonstrates genotoxic effect absence. Thus, Tween 80 does not induce chromosomic aberrations and it suggests that could be used, in temporary genotoxicity tests as surfactant to hydrophobic substance dilution in water. Another part of the work was the evaluation of the essential oil of S. terebinthifolius to control the fungus Colletotrichum gloeosporioidesin vitro and in vivo. The different oil concentrations were diluted in Tween 80, 8%. The oil was tested in vitro, in the concentrations of 0.05, 0.10, 0.25 and 0.50%, with regard to the mycelial growth velocity index in BDA culture media. The fungus growth inhibition was directly proportional to the concentrations and the 0.50% concentration inhibited 79.07% of the growth. In the in vivo test the post harvest period of papaya fruits treated with 0.50% of the oil was evaluated. These fruits had not been indicated for commercialization because the characteristics of high values of mass loss and firmness and also phytotoxicity symptoms. Therefore, because of the oil inhibitory capacity, it is suggested studies with the same oil in less phytotoxicity sensitive fruits